Tax compliance in a self-assessment system in the context of South Africa and Indonesia - Tekolo, Tukisang Ambrose (Rhodes University, 2026)
Tax compliance is essential for both wealthy and developing nations to fulfil the requirements of the social contract. Public service delivery, fiscal deficit reduction and growth require efficient tax structures, particularly in emerging economies like Indonesia and South Africa. Self-assessment systems, where taxpayers calculate the tax owing, submit the tax return and pay the tax, aim at this efficiency. Indonesia uses self-assessment systems for all its taxes, while South Africa uses the system for Value-Added Tax, Donations Tax, withholding taxes and excise duties. Indonesia’s low Tax-to-GDP ratio and South Africa’s tax gap indicate compliance concerns. This highlighted the need to examine the effectiveness of self-assessment systems by assessing strategies that both countries have implemented to address concerns with tax compliance. The study was situated within the interpretative paradigm as it sought to describe and understand tax compliance strategies implemented in relation to a self-assessment system. A qualitative methodology applied in terms of which data was thematically analysed. Data sources were in the form of publicly available materials. The study identified factors associated with tax compliance, discussed compliance problems faced by Indonesia and South Africa, and analysed the strategies that both countries implemented to address low compliance. It was found that both Indonesia and South Africa invest in tax education. Indonesia uses rehabilitative enforcement measures while those of South Africa are punitive. Technology and innovation have been applied by both countries in enhancing compliance. Tax reforms such as the Sunset Policy in Indonesia and Voluntary Disclosure Programmes in both countries have been introduced to broaden the tax base and improve compliance. Both countries promote trust-based compliance through communication and service quality. Recommendations were made to improve tax compliance in South Africa. This included strengthening taxpayer education and awareness, enhancing digital infrastructure and technological inclusion, balancing enforcement with trust-based compliance, and implementing an e-invoicing system for VAT administration.
Keywords: Taxpayer compliance (http://id.loc.gov/authorities/subjects/sh86005848); Value-added tax (http://id.loc.gov/authorities/subjects/sh85141932); Taxation--Indonesia (http://id.loc.gov/authorities/subjects/sh2010115531); Taxation--South Africa; Taxation; Tax-to-GDP ratio (https://www.wikidata.org/wiki/Q3911187); Self-assessment system (https://www.wikidata.org/wiki/Q11578021)